2022
DOI: 10.1088/1755-1315/972/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Based Application for Safety Training at Shipyards

Abstract: The implementation of safety training is conducted to provide knowledge on the importance of safety for its employees. However, the implementation of safety training requires many consumable things such as a lot of Portable Fire Extinguishers (PFE) that increase the operational cost and trigger the environmental pollution. This research aims to design a safety simulation based on VR (virtual reality) to provide an immersive experience for safety training and reduce the training costs. It was obtained that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Regarding the contributions of these technologies to occupational safety, they include solutions which involve monitoring the work environment and physical working conditions [14][15][16][17][18][19][28][29][30][31][49][50][51], communication support [20,21,[34][35][36][37][38][39][40]56,57,61], workplace inspection [25][26][27]42,43], task monitoring [23,33,[44][45][46]58], occupational training [15,[53][54][55][56][57]59,[62][63][64]66], and protective clothing [67][68]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the contributions of these technologies to occupational safety, they include solutions which involve monitoring the work environment and physical working conditions [14][15][16][17][18][19][28][29][30][31][49][50][51], communication support [20,21,[34][35][36][37][38][39][40]56,57,61], workplace inspection [25][26][27]42,43], task monitoring [23,33,[44][45][46]58], occupational training [15,[53][54][55][56][57]59,[62][63][64]66], and protective clothing [67][68]…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that more than half of the trainees positively evaluated the VR training and reported having positive emotions during the training session. According to Wahidi et al, (2022), A comparison of conventional occupational safety training with work-based safety training in virtual reality technology is seen from the seven variables in the training process: space, safety, environment, time, equipment, simulation, and assessment. VR-based work safety training simulations can improve the theoretical knowledge of occupational safety trainees by as much as 14.05% based on written pre-test and post-test results.…”
Section: Z Pmentioning
confidence: 99%